The aldosteronoma resolution score predicts the prognosis of hypertension under two surgical procedures - Huang, Yifan; Huang, Qianhao; Xie, Yijie; Ouyang, Chaoyue; Chen, Yuedong; Huang, Chao (Frontiers in Endocrinology, 2025)
BackgroundPrimary aldosteronism (PA) is a leading cause of secondary hypertension, and aldosterone-producing adenoma (APA) is the most prevalent subtype. Surgical intervention is the primary treatment modality. However, a subset of patients fails to achieve normotension postoperatively. The Aldosteronoma Resolution Score (ARS), a preoperative predictive model, was used to forecast postoperative hypertension resolution. This study aims to validate the accuracy of the ARS in predicting hypertension resolution in Asian patients undergoing different surgical approaches.MethodsWe conducted a retrospective review of 129 patients diagnosed with APA who underwent adrenal surgery. After excluding patients with incomplete data or insufficient follow-up, 83 patients were included in the analysis. Patients were stratified into two groups based on surgical approach: partial adrenalectomy and total adrenalectomy. Clinical and blood pressure data were collected at baseline and 6 months postoperatively.ResultsAt the 6-month follow-up, 62.65% (52/83) of patients achieved normotension without medication, while 37.35% (31/83) required continued antihypertensive therapy. Multivariate logistic regression analysis identified that patients achieving complete hypertension resolution were significantly more likely to have: preoperative use of ≤2 antihypertensive medications, hypertension duration ≤6 years, and BMI ≤25 kg/m². The predictive accuracy of the ARS, evaluated using the area under the receiver operating characteristic curve (AUC), was 0.866 for the overall cohort. Among the 49 patients (59.0%) who underwent partial adrenalectomy, 36.73% required antihypertensive medication, with an ARS AUC of 0.839. Among the 34 patients (41.0%) who underwent total adrenalectomy, 61.76% achieved normotension, with an ARS AUC of 0.897. No significant difference was observed in postoperative blood pressure outcomes between the two surgical approaches (P = 0.889), nor did the surgical approach affect the predictive accuracy of the ARS (P = 0.461).ConclusionOur study validates the ARS, originally derived from Western populations, as a reliable preoperative predictor of hypertension resolution following adrenalectomy in Asian patients with APA. Furthermore, both partial and total adrenalectomy demonstrated comparable efficacy in achieving blood pressure control. These findings support the broad applicability of the ARS across diverse patient populations and surgical approaches.